142k views
5 votes
How do I solve this?

How do I solve this?-example-1
User Benoittr
by
4.7k points

1 Answer

2 votes

Answer:

The other end point is
(-3,5)

Explanation:

For two points
(x_1,y_1) and
(x_2,y_2)

The mid point
(x,y)=((x_1+x_2)/2,(y_1+y_2)/2)

For the mid point
(x,y)=(-1,1)

and
(x_1,y_1)=(1,-3)


(x_2,y_2)=?


(-1,1)=((1+x_2)/2,(-3+y_2)/2)


(1+x_2)/2=-1\\\\1+x_2=-2\\\\x_2=-2-1\\\\x_2=-3

And


(-3+y_2)/2=1\\\\-3+y_2=2\\\\y_2=2+3\\\\y_2=5\\

So, the other end point is
(-3,5)

User Yousef Altaf
by
5.5k points